2021
DOI: 10.1097/md.0000000000025104
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of oxidative stress parameters in breast and colon cancer

Abstract: Our aim in this study was to investigate the relationship between serum ischemia modified albumin (IMA) levels with oxidative stress parameters [protein carbonyl (PCO), advanced protein oxidation products (AOPPs), malondialdehyde (MDA), total nitric oxide (NOx), prooxidant-antioxidant balance (PAB), and ferric reducing of antioxidant power (FRAP)] in breast cancer (BC) and colon cancer (CC). In total, 90 patients undergoing surgical treatment for BC (n = 45) or CC (n = 45) and 35 healthy controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 37 publications
2
26
0
1
Order By: Relevance
“…The observed association of sarcopenia with high plasma MDA at 6-month is consistent with increased MDA levels in sarcopenic elderly compared to their nonsarcopenic counterparts [ 38 , 77 ]. Furthermore, plasma MDA has been suggested as a biomarker of cancer and tumour progression [ 78 – 80 ]. Also, a significant increase was observed in patients undergoing treatment for cervical cancer as compared to pretreatment levels [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observed association of sarcopenia with high plasma MDA at 6-month is consistent with increased MDA levels in sarcopenic elderly compared to their nonsarcopenic counterparts [ 38 , 77 ]. Furthermore, plasma MDA has been suggested as a biomarker of cancer and tumour progression [ 78 – 80 ]. Also, a significant increase was observed in patients undergoing treatment for cervical cancer as compared to pretreatment levels [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the antioxidant/oxidative parameters of tumors are prognostically crucial in many types of cancer. These parameters can be assessed via the detection of wellknown oxidative markers of proteins, such as protein carbonyls, advanced oxidation protein products, and IMA [158]. Many investigations have demonstrated that IMA levels significantly increased in different proliferative diseases (Table 5).…”
Section: Obstetrics and Gynecologymentioning
confidence: 99%
“…According to the ROC analysis, IMA has sensitivity above 80% as an auxiliary biomarker in the diagnosis of such diseases as breast and colon cancer [158]. It can be effective in demonstrating hypoxia in patients with acute leukemia [166] and used as an additional indicator for the prognosis of the myelodysplastic syndrome [167].…”
Section: Obstetrics and Gynecologymentioning
confidence: 99%
“…Indeed, differences in tumour microenvironment might translate into distinct responsiveness to cell death. Persistent oxidative stress is a common feature of CRC cells which is known to be exacerbated by some natural antioxidant [58,59]. It is undoubtedly intriguing how the antioxidant Egt induces ROS, which itself seem to fail to quench completely, causing CRC cell death.…”
Section: Discussionmentioning
confidence: 99%